Best Answer

The question contains an expression but since there is no equality sign, there is no equation and so nothing that can be solved..

User Avatar

Wiki User

7y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What does 3(4x - 3) - 19 8x - 4 equal when solved?
Write your answer...
Still have questions?
magnify glass
Related questions

What is factorization of 8x plus 26x - 7?

8x + 26x - 7 = 34x - 7 = (√34x)2 - (√7)2 = √34x - √7)(√34x + √7)

What does x equal in 42x plus 1 equals 8x minus 1?

42x + 1 = 8x - 1Subtract 1 from each side:42x = 8x - 2Subtract 8x from each side:34x = -2Divide each side by 34:x = -2/34 = -1/17

8x-9 -2x plus 11?

8x-9 -2x plus 11 when solved mathematically is equal to 6x + 2.

What is 6x plus 3 equals 8x plus 14?

6x plus 3 equals 8x plus 14 when solved mathematically is equal to x = -5.5.

What is the first step in solving 19 plus 8X equals 91?

subtract 19 from 91. this will give you 8X equals 72. then you divide 72 by 8, and therefore X will equal to 9

3x plus 5x equals 34?

3x + 5x = 348x = 34x = 34/8x = 17/4 orx = 4.25

What is 8x-36 equal?

8x-36 equal = -28

How do you solve 8x plus 32?

8x+32 is an expession and can't be solved unless a value for x is given.

What is equivalent to 8x?

x*8 is equal to 8x.

6x plus 9 equals -19-8x what is the value of x?

This equation that you are asking of is a complex equation that inverse operations are needed in to solve it. First, use the inverse operation and add 8x to 6x. The 8x on the right side of the equation will cancel out. The 6x and the 8x will equal to 14x: 8x+6x+9=-19-8x+8x which now equals 14x+9= -19Secondly, eliminate the constant terms by subtracting 9 on both sides of the equation: 14x+9-9= -19-9Now the problem is 14x= -28Third step - isolate the variable and divide 14 by -28. X should now equal -2.14x/14= -28/14 which should equal x= -2You can check and see that this is accurate by multiplying -2 to each coefficient that had x as their variable: 6(-2)+9=-19-8(-2)-12+9= -19+16 which equals -3=-3

What is x-3x plus 2x-8x equal?


-8x plus 4y equals 64?

This can't be solved. You have two varibles.